Analisis Kontrastif Kalimat Pasif Bahasa Indonesia dengan Bahasa Inggris - Suprato, Djuria (Humaniora, 2012)
The difficulty of a teacher to teach a second language to students can be addressed by contrastive analysis, where it is assumed that learning a second language is influenced by the first language acquisition. The purpose of this article is to describe the level of a comparable degree of passive sentences in Indonesian and English to provide benefits as a reference in the teaching of English as a second language. This study was conducted with qualitative methods, the reference library of resources Indonesian and English. Passive Sentences in Indonesian views of the structure using the "di", "ter" or "ke", in English we use "to be + past participle" depends on the time it happened. Context of the sentence must be considered so that the meaning contained in them can be understood. Once analyzed and searched in the matching and comparison of passive sentences in Indonesian and English, the authors have found similarities and differences which can be structurally or pragmatically.